Microbiota associated with the skin, gills, and gut of the fish Parachondrostoma toxostoma from the Rhône basin. (8th December 2019) - Guivier, Emmanuel; Pech, Nicolas; Chappaz, Rémi; Gilles, André
Abstract: The close relationships between hosts and their microbiota underlie the current concept of holobionts. This biological entity enlarges our perception of the genomic diversity supported by individuals/species and the potential abilities of hosts to respond to the environment. We investigated a total of 54 specimens of the sofie fish Parachrondrostoma toxostoma (Pt) for the taxonomic and functional composition of microbiota associated with the skin, gills, and gut tissues. Five wild populations from the Ardèche and Durance river basins in the Mediterranean part of the large catchment of the Rhône (southern France) were compared. We found that the skin microbiota was more diverse and variable in bacterial community composition than the gut microbiota. These differences suggest that different deterministic factors underlie the composition of these bacterial communities, resulting in tissue‐specific variation of the microbiota composition between wild fish populations inhabiting two rivers. Microbiota diversity and composition differed between wild Pt populations at both regional and local spatial scales. Using the Picrust tool, the taxonomic variation of the microbiota composition in the river fish populations could be associated with the enrichment of predicted metabolic pathways. In particular, carbohydrate metabolism was more represented and xenobiotic biodegradation pathways less represented in the gut microbiota of Pt populations from the Ardèche than of those from the Durance. This result suggests variability in the ability to acclimate to environmental features through the assimilation of food resources from plants and the detoxification of xenobiotic components. This study opens perspectives in the detection of subtle shifts in environmental features through the description of the microbiota composition, and in the potential prediction of the functional capacities of species to acclimate.